Increasing Employees’ Performance Through Punishment System At Nusa Dua Beach Hotel & Spa - Rahayuda, Putu Gilang; Ernawati, Ni Made; Sutama, I Ketut (Jurnal Sains Terapan Pariwisata, 2022)
Purpose: This research was conducted at Nusa Dua Beach Hotel & Spa, a 5-star hotel in Nusa Dua, Badung, Bali. This research focuses on increasing employee performance through the punishment system at Nusa Dua Beach Hotel & Spa. This research aimed to identify the punishment system implemented at the Nusa Dua Beach Hotel & Spa and to discover the effect of punishment on employee performance in Nusa Dua Beach Hotel & Spa.Methods: The sample used was 72 respondents, with several forms of collecting data: observation, conducting interviews with human resources managers and employees, documentation, literature study, and distributing questionnaires. Data analysis techniques used in this research are descriptive qualitative analysis and quantitative analysis with a simple linear regression method.Results and discussion: The results of this research could be concluded that the punishment system variable affects increasing employees’ performance variable even though its implementation is still lacking. The management needs to improve the punishment system for employees to increase employees’ performance in Nusa Dua Beach Hotel & Spa.Implication: The punishment system positively and significantly affects the employees' performance at Nusa Dua Beach Hotel & Spa.